Concurrent environmental enrichment and chronic restraint stress: Effects on innate anxiety and depressive‐like behavior in male adolescent mice. Issue 8 (19th September 2020) - Mao, Yu; Chen, Yanmei; Yang, Xiaomi; Wang, Jianhong; Ge, Longjiao; Fu, Juan; Sun, Huaying; Ma, Yuanye
Abstract: Adolescence is a period that exhibits both vulnerability and adaptation to environmental stimulus. This study explored the co‐existence effect of environmental enrichment (EE) and restraint stress (RS) on innate anxiety and depressive‐like behavior in adolescent mice. Male ICR mice were treated with daily EE and RS (4 h/d or 8 h/d) for 2 or 4 weeks from early adolescence (postnatal day 30) and emotional behaviors were evaluated 24 h after the end of treatment. 4 weeks of 8 h RS treatment decreased immobility time in forced swimming test, demonstrating an antidepressant‐like effect. For 2 weeks of treatment, 8 h RS significantly reduced the time spent in the lighted compartment of the light‐dark box, indicating an increased anxiety level. These results show that under the present experimental design, RS treatment with different duration could have different effect on mice emotion‐related behavior, but there was no interaction between EE and RS. Abstract : This research aimed to reveal the concurrent effect of enriched environment and chronic restraint stress on emotion related behavior in adolescence mice. The results indicated that restraint stress could increase anxiety level but decrease the depressive level according to different duration of restraint stress, however there was no interaction between enriched environment and restraint stress. The result shows behavior plasticity in adolescent mice to chronic restraint stress.